Person and situation effects in predicting outgroup prejudice and avoidance during the COVID-19 pandemic. (April 2021) - Meleady, Rose; Hodson, Gordon; Earle, Megan
Abstract: Recent theories of intergroup relations suggest that factors relevant to disease, disgust, and contagion predict prejudice towards ethnic outgroups. The current research explored the influence of contextual pathogen threat and individual differences in threat sensitivity on outgroup prejudice and avoidance in the context of the COVID-19 pandemic. Data were collected from a sample of British adults in June 2020 ( N  = 524). A multi-level approach was employed to capture differences in confirmed COVID-19 cases across different regions in the UK. Results demonstrated that even in a "strong" pandemic context, individual differences in both disgust sensitivity (DS) and intergroup disgust sensitivity (ITG-DS) explained variability in outgroup distancing. Subjective perceptions of contextual pathogen prevalence, but not actual infection rates, also predicted greater outgroup avoidance. However, a significant cross-level interaction revealed that DS predicted outgroup distancing in regions with higher numbers of confirmed COVID-19 cases, but not in areas of lower infection. Thus, individual differences in pathogen avoidance may be especially influential under high situational pathogen stress. There was also some evidence that pathogen threat also predicted greater ingroup attraction. Results provide important insights into factors that promote or inhibit positive intergroup relations during pandemics.